Factors Influencing Cage Escape Behavior in a Migrating Passerine at a Stop-Over Site - Dariusz Jakubas; Katarzyna Wojczulanis-Jakubas; Marta Witkowska; Aleksandra Lesiewicz; Brygida Manikowska-Ślepowrońska; Izabela Wiśniowska; Łukasz J. Binkowski (Animals, 2025)
Cognitive abilities play a critical role for migratory birds encountering unfamiliar habitats at stop-over sites. We investigated factors (age, sex, fuel reserves, vertical/horizontal activity, and mercury level) affecting cognitive abilities behavior (problem-solving task—escaping from an experimental cage) in a long-distance migratory passerine, the sedge warbler (Acrocephalus schoenobaenus) at an autumn stop-over site. During the experiment, after two minutes of acclimatization, we remotely opened the door of the cage and recorded whether each bird escaped or remained in the cage. A mixed-effects Cox model revealed that the probability of escaping from the cage was significantly affected by variance in horizontal movements along the horizontal axis of the cage during the acclimatization phase (in models for all individuals and immatures) and sex (in immatures). Individuals moving more were more likely to escape from the cage. Immature males, at any given time, were 2.3 times more likely to escape from the cage than females. We interpreted this in the context of risk-partitioning with males adopting a high-risk, high-reward strategy and females using a low-risk, low-reward strategy, which may be associated with a predisposition for sex-specific roles in breeding. The repeatability of escape response was low (7.3%) for the same recaptured individuals.